Notary’s Authority Concerning Reporting Suspicious Transactions in the Prevention and Eradication of Money Laundering Crimes - I Gusti Agung Ayu Winda Savitri Adi; I Gede Yusa; Anak Agung Sagung Laksmi Dewi (Sociological Jurisprudence Journal, 2024)
The purpose of this study is to determine the authority of Notaries in reporting transactions related to suspected money laundering and to analyze the application of the principle of confidentiality of Notary positions related to their authority in reporting transactions with suspected money laundering. The research method used is normative law with the statute, analytical, conceptual, and comparative approaches. The study results show that Notaries have the authority and are responsible for reporting suspicious transactions suspected of money laundering. The authority is related to the confidentiality of Notary positions, which experience conflicting norms between PP No. 43 of 2015 and UUJN, resulting in legal uncertainty. UUJN can set aside PP No. 43 of 2015 based on its lower hierarchy. However, because the crime of money laundering concerns the public interest, the confidentiality of the position can be set aside. In terms of reporting the alleged crime, Notaries are required to obtain legal protection as determined by statutory regulations.